2004
DOI: 10.1097/01.asn.0000125613.96927.38
|View full text |Cite
|
Sign up to set email alerts
|

Increased Activity of cGMP-Specific Phosphodiesterase (PDE5) Contributes to Resistance to Atrial Natriuretic Peptide Natriuresis in the Pregnant Rat

Abstract: Abstract. Increased cGMP-specific phosphodiesterase (PDE5) activity in renal inner medullary collecting duct (IMCD) cells contributes to resistance to atrial natriuretic peptide (ANP) and the excessive sodium retention seen in experimental nephrotic syndrome and liver cirrhosis. Normal pregnancy is also accompanied by sodium retention and plasma volume expansion, and pregnant rats are resistant to the natriuretic action of ANP. The authors investigated a possible role of increased renal PDE5 activity in the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
21
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 28 publications
5
21
1
Order By: Relevance
“…These changes closely resemble the responses in normal pregnancy. We also found that these changes are accompanied by an increase in renal medullary PDE5 mRNA and protein expression, similar to the changes in PDE5 protein abundance we previously observed in normal pregnant rats (23). Therefore, these data suggest that a primary underfill signal causes an increase in renal inner medullary PDE5, leading to loss of tubular natriuretic responses.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…These changes closely resemble the responses in normal pregnancy. We also found that these changes are accompanied by an increase in renal medullary PDE5 mRNA and protein expression, similar to the changes in PDE5 protein abundance we previously observed in normal pregnant rats (23). Therefore, these data suggest that a primary underfill signal causes an increase in renal inner medullary PDE5, leading to loss of tubular natriuretic responses.…”
Section: Discussionsupporting
confidence: 70%
“…In IMCD cells isolated from pregnant rats, there is blunting of the cGMP response to both atrial natriuretic peptide (ANP) and a nitric oxide (NO) donor (sodium nitroprusside), and this is normalized by inhibition of PDE5 (23,29). We suggest that this increased inner medullary PDE5 inhibits all cGMP-mediated natriuretic responses, contributing to the volume expansion of normal pregnancy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We found no change in renal cortical NCC (an aldosterone responsive sodium transporter in the distal tubule) with NIF-induced chronic vasodilation in the present study, although Wang et al did report increased NCC using a much higher dose of NIF (37). However, in normal pregnancy, we also observed that cortical NCC was unchanged (38); thus, the chronic systemic vasodilation in virgin female rats in the present study recapitulates the changes seen in normal pregnancy (24,38). The renal sodium retention of normal pregnancy is accompanied by early and sustained activation of the RAAS (5, 17, 34), a physiological response to an "underfill" signal.…”
Section: Discussioncontrasting
confidence: 41%
“…We have reported increased abundance and activity of phosphodiesterase 5A (PDE5A) in the inner medulla of the normal pregnant kidney (24). Increased PDE5A activity in the inner medulla blunts the cGMP-mediated natriuretic actions of atrial natriuretic peptide (ANP) and nitric oxide (NO) in the pregnant rat (15,24,33).…”
mentioning
confidence: 99%